Phylogeny of Geophagini (Cichliformes: Cichlidae: Cichlinae) using encephalon gross morphology. - Oliveira, Rianne Caroline de (2020)
Several studies have presented phylogeny of Geophagini based on morphological and molecular characters; however, neuroanatomical characters have not been explored for the tribe yet. Fish encephalon shows interspecific morphological variation, even in related groups, and can be used to build cladograms. The phylogeny of Geophagini is presented using the neuroanatomical characters mapped on a previous cladogram. This approach showed how the encephalon of Geophagini species have diversified among clades and how ecological features of some species can be related to changes (increase or decrease) of a particular structure. The morphological description of the encephalon of Geophagus sveni was also performed, with an illustration of the major encephalon structures and the origin of the cranial nerves, as well as a comparison of the morphometric differences between males and females.